THE EFFECT OF VOCABULARY MASTERY AND LEARNING MOTIVATION ON THE ABILITY TO WRITE DESCRIPTIVE TEXT IN ENGLISH - Gustiya Gandha Metri (FKIP, Universitas Palangka Raya, 2022)
This study aims to determine: 1) The effect of vocabulary mastery and learning motivation on the ability to write descriptive text in English for private junior high school students in Bekasi; 2) The effect of vocabulary mastery on the ability to write descriptive text in English for private junior high school students in Bekasi city; 3) The effect of learning motivation on the ability to write descriptive text in English for private junior high school students in Bekasi city. The sample in this study were 75 students with multiple linear regression statistical models and the method used in this study was the simple random sampling method. The results showed that: 1) There is a significant influence on vocabulary mastery and learning motivation together on the ability to write descriptive text in English for private junior high school students in Bekasi City. This is evidenced by the acquisition of the value Sig = 0.000 <0.05 and Fcount = 27.749. 2) There is a significant effect of vocabulary mastery on the ability to write descriptive text in English for private junior high school students in Bekasi City. This is evidenced by the acquisition of the value of Sig = 0.000 <0.05 and tcount = 3.938. and 3) There is a significant influence of learning motivation on the ability to write descriptive text in English for private junior high school students in Bekasi City. This is evidenced by the acquisition of the value of Sig = 0.031 <0.05 and tcount = 5.567.